DNA BARCODING REVEALS THE IDENTITY OF BIRD REMAINS FROM THE BIRD STRIKE INCIDENT IN INDONESIA - Yohanna Yohanna; Mohammad Irham; Indra Gunawan; Anton Saryono; Yusuf Tawakal; Dewi Malia Prawiradilaga; Anik Budhi Dharmayanthi (Masyarakat Zoologi Indonesia, 2022)
A bird strike refers to a collision between birds and a plane. This incident risks the flight because it could damage the aircraft and threaten airlines' safety. The airports have been implementing safety measures to prevent and minimise the risk of bird strikes, such as monitoring wildlife, habitat management, and using various types and techniques of bird deterrents. While monitoring birds will provide baseline data to estimate the level of risk for each species, it is vital to have data on birds directly involved in bird strikes; hence, the airport can determine more precisely which species have the most significant potential to cause bird strikes. Therefore, identifying the remains of birds from the aeroplane is essential as a safety measurement in bird strike management. In this study, we applied DNA barcoding using the cytochrome oxidase I barcode gene to identify the birds' remains. Samples consisting of three feathers and tissues collected from the plane were analysed. The Cytochrome Oxidase I sequence analysis showed that all six samples were identified as Haliaeetus leucogaster (White-bellied sea eagle) with percentage identity 100% after BLAST to NCBI. We also identified the feathers by comparing them with reference specimens, which showed that they came from wing feathers of H. leucogaster. We concluded that DNA barcoding could be used to identify the species of bird involved in bird strike incidents; therefore airport could incorporated DNA barcoding technique on their wildlife hazard management.